Implementation of Criminal Responsibility Arrangements for Perpetrators of Prostitution - Kojongian, Rahayu (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
Prostitution is an act that is morally and mentally damaging which can also destroy the integrity of the family. Still, positive law itself does not prohibit perpetrators of the practice of prostitution but only prohibits those who provide a place or facilitate the practice of prostitution. This research aims to understand and find out the philosophy of the existence of criminal liability regulations for perpetrators of prostitution. The research method used is Empirical Legal Research using empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Because this research examines people in their living relationships in society, the empirical legal research method can be said to be sociological legal research taken from facts in a society, legal entity or government agency. The research results show that the provisions of the Criminal Code can only be used to trap pimps/pimps/prostitute prostitutes. Meanwhile, articles that can be used to trap prostitutes/users are regulated in each regional regulation. So, the handling of prostitution cases depends on the location of the area where the crime occurred. Apart from that, criminal charges for prostitutes can be related to the article on adultery, which is regulated in Article 284 of the Criminal Code.